1988
DOI: 10.1164/ajrccm/137.2.380
|View full text |Cite
|
Sign up to set email alerts
|

CT Measurements of Lung Density in Life Can Quantitate Distal Airspace Enlargement—An Essential Defining Feature of Human Emphysema

Abstract: We used a computerized microscopic image analysis system to directly measure the surface area of distal air spaces in methacrylate-embedded blocks randomly selected from inflation-fixed lobes that were resected from 45 patients as treatment of their peripheral lung tumors. In 28 of these patients, a preoperative computer tomography (CT) scan, at 6 and 10 cm below the sternal notch, was used to generate frequency histograms of CT numbers (measured as EMI units), a measure of lung density, in pixels from the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
209
1
4

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(223 citation statements)
references
References 7 publications
9
209
1
4
Order By: Relevance
“…GOULD et al [33] reported the first successful application of a quantitative CT technique that correlated well with pathological evidence of emphysema.…”
Section: Image Analysismentioning
confidence: 97%
“…GOULD et al [33] reported the first successful application of a quantitative CT technique that correlated well with pathological evidence of emphysema.…”
Section: Image Analysismentioning
confidence: 97%
“…Ever since the work by Hayhurst and coworkers (31), Gould and coworkers (32), and Mü ller and coworkers (33) showed that the extent of emphysema could be measured using CT, these techniques have been applied to studies of COPD. These early studies showed that by using either a threshold technique whereby any lung voxels with X-ray attenuation values less than a given cutoff (e.g., 2910 HU) (33) or the X-ray attenuation value (measured in HU) at a given percentile point of the distribution of X-ray attenuation values (e.g., 5th percentile point) (31,32) correlated with extent of emphysema measured using quantitative pathology.…”
Section: Phenotyping Of Copd Using Computed Tomographymentioning
confidence: 99%
“…These early studies showed that by using either a threshold technique whereby any lung voxels with X-ray attenuation values less than a given cutoff (e.g., 2910 HU) (33) or the X-ray attenuation value (measured in HU) at a given percentile point of the distribution of X-ray attenuation values (e.g., 5th percentile point) (31,32) correlated with extent of emphysema measured using quantitative pathology. These original studies have been refined over the years with different threshold points being redefined (9,34,35), as CT scanners and image reconstruction techniques have evolved but the basic principle remains the same, that low attenuating areas on CT are indicative of lung tissue destruction ( Figure 5).…”
Section: Phenotyping Of Copd Using Computed Tomographymentioning
confidence: 99%
“…Mean lung density, however, is not the only densitometric parameter which can be extracted from the CT data. Pixel index analysis [3,4,14] and the lowest 10th percentile of the frequency distribution of densities [15] have shown promising results in the assessment of emphysema.If densitometry of the lung is used for diagnosis and follow-up of pulmonary emphysema or interstitial lung disease, the overall precision of the procedure has to be established. Reproducibility errors due to instrumental and technical factors have generally been considered to be smaller than patient-related factors.…”
mentioning
confidence: 99%
“…Mean lung density, however, is not the only densitometric parameter which can be extracted from the CT data. Pixel index analysis [3,4,14] and the lowest 10th percentile of the frequency distribution of densities [15] have shown promising results in the assessment of emphysema.…”
mentioning
confidence: 99%